Cyclobutene based macrocycles. (19th November 2020) - Wang, Pan; Lu, Ruqiang; France-Lanord, Arthur; Wang, Yanming; Zhou, Jingjing; Grossman, Jeffrey C.; Swager, Timothy M.
Abstract : Nanoscopic macrocycles could have unusual magnetic, optical, and electronic properties when compared to their linear counterparts. Abstract : Nanoscopic macrocycles could have unusual magnetic, optical, and electronic properties when compared to their linear counterparts. Conjugated π-systems in unsaturated macrocycles are particularly interesting as they have no end groups that limit electronic delocalization in equivalent linear oligomers. The rigid four-membered ring structure in 3, 4-bis(methylene)cyclobutene with vicinal connections provides a vertex with an angle slightly less than 90°, which promotes macrocycle formation. We report herein a facile high-yielding synthesis of a series of 3, 4-bis(methylene)cyclobutene-base π-conjugation macrocycles. The structure–property studies reveal that the smaller macrocycles are rigid crystalline frameworks and display symmetrical conformations in solution. The electrochemical, photophysical and magnetic properties of these macrocycles were also studied with a framework of characterization methods, revealing their size- and linkage-dependent properties. Density functional theory (DFT) calculations and molecular dynamics (MD) simulations at the molecular level suggest that several possible configurations are possible for macrocycles with larger ring sizes.